INDONESIA - FREEPORT ECONOMIC DISPUTE - Farah Redina Azaria (UIN ALAUDDIN MAKASSAR, 2020)
PT. Freeport Indonesia began operating in the Mimika district in Papua Province at the Gresberg mining. Their cooperation with Indonesia was marked with a contract of work I (Kontrak Karya / KK), with contract period of 30 years. The contract was made after the legalization of the investment LAW on 7 April 1967. This cooperation had been going long when KK II was established. However, in 2017 there was a change of regulation of natural resources management of Indonesia namely IUPK (Izin Usaha Pertambangan Khusus). This regulation initiated debate between Freeport and Indonesia government to reach a consensus. The method used to collect data in this study is qualitative method. Using mercantilist theory, this study suggests that state income and gains are major aspect in international cooperation.Keywords : Indonesia, Freeport, Mercantilism, and Foreign Policy